Post-Truth Politics in International Relations: The Impact of Disinformation on Global Diplomacy - Ahmad Salman Farid (Pt. Anagata Sembagi Education, 2026)
The proliferation of disinformation in the digital age has fundamentally reshaped the landscape of international relations and global diplomacy. This article examines how post-truth politics, characterized by the systematic subversion of epistemic norms and the weaponization of falsehoods, undermines the liberal international order and erodes trust among state and non-state actors. Drawing on an interdisciplinary synthesis of recent empirical research (2021–2024), we analyze the mechanisms through which disinformation campaigns distort diplomatic communication, destabilize alliances, and exploit democratic vulnerabilities. We further explore state-sponsored disinformation as a tool of geopolitical competition, with particular attention to computational propaganda, deepfakes, and social media manipulation. Our findings suggest that misinformation not only threatens individual democracies but poses systemic risks to multilateral cooperation, international norms, and the epistemic integrity of global governance. We conclude by discussing emerging counter-strategies, including prebunking, media literacy, and institutional transparency frameworks.